Pengaruh Metode Scaffolding Berbasis Konstruktivisme Terhadap Hasil Belajar Siswa Materi Barisan dan Deret Aritmatika (Universitas Muhammadiyah Palembang, 2021)
This type of research is experimental. The population in this study were all class VIII students of MTs Nurul Islam Bayung Lencir in the academic year 2020/2021 with a sample of class VIIIA as the experimental class and VIIIB as the control class. After learning using the constructivism-based scaffolding method, the mean value of , and the standard deviation value is While learning using the expository method obtained an average value of and the standard deviation is . Based on the criteria for testing the hypothesis, it shows that the price of = and this means that is in the rejection area of , which means that is accepted. Thus the hypothesis which states there is a significant effect of the constructivism-based scaffolding method on student mathematics learning outcomes in the arithmetic sequence and series material in class VIII MTs Nurul Islam Bayung Lencir is accepted as true.